2005
DOI: 10.1002/mus.20459
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ or long‐term effects of adult myoblast transfer on properties of reinnervated skeletal muscles

Abstract: Skeletal muscle demonstrates a force deficit after repair of injured peripheral nerves. Data from the literature indicate that myoblast transfer enhances recovery of muscle function. Thus, we tested the hypothesis that transfer of adult myoblasts improves the properties of reinnervated rabbit tibialis anterior (TA) muscles in both the short term (4 months) and long term (14 months). Two months after transection and immediate suture of the common peroneal nerve, TA muscles were made to degenerate by cardiotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Our data suggested that the transplanted MPCs formed myotubes improved muscle function, but did not improve muscle mass. Whether the loss of muscle mass can be reduced when a larger number of cultured MPCs [22] or whether freshly isolated cells are injected [59] remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our data suggested that the transplanted MPCs formed myotubes improved muscle function, but did not improve muscle mass. Whether the loss of muscle mass can be reduced when a larger number of cultured MPCs [22] or whether freshly isolated cells are injected [59] remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of denervated muscle fibers can also increase the proportion of non-contractile elements and decreased specific force [22]. However, it is unlikely that nerve injury contributes to the loss of specific force, as results from our previous study and others showed that nerve injury under similar ischemic condition is only acute and force generated through direct muscle stimulation is similar to that generated through nerve stimulation at 2 wk after TK application, suggesting a lack of nerve injury at this time point [57].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This simplicity, to be obtained and expanded in vitro, facilitated the use of myoblasts for cell transplantation. Myoblast transplantation was studied by several different teams in a wide range of animal models such as mice [9], rats [10,11], dogs [12,13], monkeys [14], rabbits [15,16], and pigs [17]. The selective removal of satellite cells in mice makes myofiber regeneration impossible [18][19][20], demonstrating the pivotal and seemingly exclusive role of satellite cells and their progeny, myoblasts, in myofiber regeneration.…”
Section: Cells With Myogenic Capacity: Candidates For Transplantamentioning
confidence: 99%
“…So far, myoblasts were the only myogenic cells that were proved unequivocally to engraft in humans and produce myofibers expressing donor-derived dystrophin in DMD patients [10][11][12][13] (Figures 2 and 3). Unlike the other cells that will be described below, myoblasts have been studied by several different teams in a wide range of animal models such as mice [61], rats [62,63], dogs [64,65], monkeys [66], rabbits [67,68], and pigs [69].…”
Section: Satellite Cells and Myoblasts: The Mainstay Of Myofibermentioning
confidence: 99%